2018
DOI: 10.2298/csis171015021j
|View full text |Cite
|
Sign up to set email alerts
|

An optimized method of HDFS for massive small files storage

Abstract: The development of the Internet-of-Things (IoT) and the Cyber-Physical System (CPS) has greatly facilitated many aspects of technological applications and development. This may lead to significant data growth, especially for small files. The analysis and processing of a large number of small files has become a crucial part of the development of IoT and CPS. Hadoop Distributed File Systems have become powerful platforms to store a larger amount of big data. However, this method has a number of issues when deali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Hadoop's dynamic hashing and order-preserving operations can efficiently handle thousands of small files. Weipeng Jing et al [14] suggested a dynamic queue method (DQSF) based on the analytical hierarchical process, in which small files are classified and processed according to their size. Jian-Feng Peng et al [15] tackle the HDFS small file issue by merging related small files and caching frequently accessed data to reduce small file access time.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hadoop's dynamic hashing and order-preserving operations can efficiently handle thousands of small files. Weipeng Jing et al [14] suggested a dynamic queue method (DQSF) based on the analytical hierarchical process, in which small files are classified and processed according to their size. Jian-Feng Peng et al [15] tackle the HDFS small file issue by merging related small files and caching frequently accessed data to reduce small file access time.…”
Section: Related Workmentioning
confidence: 99%
“…Technique to handle Massive Small Files [14] -DQFS: Dynamic queues are used for the variable sized small files.…”
Section: Fast Access Containermentioning
confidence: 99%
“…Their solution includes a file merging algorithm based on temporal continuity, an index structure to retrieve small files, and a prefetching mechanism to improve file reading and writing. Some of these archiving systems, such as LHF [34], DQSF [21], [19], [9], before merging the files classify them or rely on some distributions criteria that help to optimize the storage or access efficiency. In case the proposed solution is built on top HDFS, it is easy to migrate to the latest version of HDFS.…”
Section: Combining Small Files Into Large Filesmentioning
confidence: 99%
“…Z. Gao proposed an effective merge strategy based hierarchy for improving small file problem on HDFS [19], which makes a radix sort on files set and merges these files orderly. Weipeng Jing [20] and his team aim to correct the problems of IoT and CPS because of small files problem.…”
Section: Related Workmentioning
confidence: 99%